KAJIAN SOSIOLOGI SASTRA DAN NILAI PENDIDIKAN NOVEL SEBELAS PATRIOT KARYA ANDREA HIRATA - Doni Uji Windiatmoko (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This article aims to describe the sociological aspects of literature and the value of character education in the novel Elbelas Patriot by Andrea Hirata. Data and data sources are in the form of novel manuscripts and research notes. The research method uses descriptive qualitative. Data analysis was carried out using content analysis. Researchers read, listen, and analyze the content or content of the manuscript in accordance with the research questions. The research results obtained are the literary sociological part of the structuralism elements of the novel in the form of theme, plot, characterization and point of view along with the educational value of patriotism. Keywords: structuralism, novels, educational value of patriotism, Andrea Hirata